The makerhub a creative industry incubator - Llanto, Carlo Martin L.
The maker hub: creative industry incubator proposes an architecture to integrate an environment to support the processes of human social interaction, business development, technological innovation, and community entrepreneurship for the development of the latent potential of the Philippines creative industry as a key component to an economy driven by innovative ideas intellectual property and creative production. This thesis is the product of a year-long endeavor to translate various concepts and theories into a design proposal to empower the Filipino community with an architecture where they can realize their creative and entrepreneurial potential particularly within the creative sectors of the Arts, Media and Functional Creations. This thesis explores the architectural design translation for collaborative inter-organizational innovation and business among co-located creative industry actors. The final CBD office-tower development integrates vertically a creative industry innovation and incubation "campus" outfitted with various venues, workspaces and facilities for creative work and business along a supporting structural and system spine. As such, issues, development challenges and design problems relating to facilities operations, creative work &space, collaboration and vertical architecture are at the corner of this study and design proposal.